THE EFFECT OF AGES ON REPRODUCTIVE PERFORMANCES OF BANANA SHRIMP, PENAEUS INDICUS - Nur, Abidin; Yudhistira, Amri; Ruliaty, Lisa; Soleh, Mohammad (Jurnal Media Akuakultur Indonesia, 2022)
Age and weight were the main target on domesticated shrimp due to affect on their reproductive performances. The objective of the present study was to know the effect of broodstock ages on reproductive performances of P. indicus. Two series experiments were conducted in the Hatchery Unit of MCBA Jepara by using the 1st generation (G-1) domesticated broodstocks at two differences ages such as 11 months (U-11) and 14 months (U-14). All maturation and spawning process were carried out under separated room-indoor system. Larva rearing and seed productions were conducted into 10 m-3 concrete tanks based on shrimp seed production protocols being developed on MCBA Jepara. Results found that the difference of broodstock ages significantly (p<0.05) affects on daily spawning rate, nauplii productions, spawning frequencies, and larvae survival, were (18.78±4,6 vs 8.85±3,69); (47.000±2.400 vs 27.421±8.555 N spawner-) ; (1.67 for 9 days vs 1.79 for 22 days) and (26.81±7,30% v 37.27s ± 1.95%), respectively. From the experiments it can be concluded that 11 months ages brooders were suggested for mass seed production purposed. However, further research of less than ages mentioned needs to take into account.